HUBUNGAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SD - Nabila, Hanna; Nurjannah, Fitri; Tia Dita Lathifa Yuwono; Putri Ramadhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between students’ learning interest and learning outcomes in the Natural and Social Sciences (IPAS) subject for fifth-grade elementary school students. Learning interest is one of the important factors that can influence students' success in the learning process. Students with a high level of learning interest tend to be more active, focused, and enthusiastic in participating in learning activities, enabling them to achieve better learning outcomes. This study employed a quantitative approach with a correlational research design. The population consisted of all fifth-grade students at a public elementary school in Pekanbaru City. Since the population was relatively small, the sampling technique used was total sampling (saturated sampling). Data were collected through questionnaires and tests. The questionnaire was used to measure students’ learning interest, while the test was used to assess learning outcomes on the topic of “Classification of Animals Based on Their Feeding Habits.” The collected data were analyzed using the Product Moment correlation test. The results of the study indicate that there is a positive relationship between learning interest and students’ learning outcomes in the IPAS subject. The higher the students’ learning interest, the higher their learning outcomes. Conversely, low learning interest may contribute to lower learning outcomes. Therefore, learning interest plays an important role in improving students’ learning outcomes in the IPAS subject.